P16. Dose distribution comparison of XiO simulated bolus vs. physically scanned bolus for head and neck patients with mask at Tygerberg Hospital. (September 2016) - Mkhize, T.; Mohlapholi, M.; Toit, M. du
Abstract : Introduction: Bolus is a tissue equivalent material that can be placed on the skin to increase dose received at depth in patient and on the skin surface. At the radiotherapy planning department, the bolus is used to improve the tumour coverage by bringing the dose (95% isodose curve) closer to the skin (mainly for superficial tumours) for head and neck patients. It is added on the TPS to the CT acquired image with mask on. The concern arose that the XiO TPS might not calculate the dose distribution correctly with the bolus added after the patient is imaged with the mask on. Materials and methods: A Rando phantom with and without bolus was scanned on the Philips Brilliance Big Bore CT using head and neck protocol. The bolus material was a super flab with density of 1.02 g/cm 3 and thickness of 0.5 cm. At CMS XiO, plans with one beam perpendicular to the phantom entering at 0° were generated. The generated plans used SAD method with 10 × 10 cm 2 field sizes on the surface. A dose of 1 Gy, normalized to 100% of Isodose curve (line) was prescribed for a 6 MV beam. Three interest points 0.5 cm apart at 1.5 cm depth were measured and their dose distributions and point doses compared. Results: The XiO drawn bolus and physically scanned bolus plan's dose distributions compared well when superimposed to one another, and their percentage error difference was ±2.35%. Conclusion: For both dose distribution and point dose measurements, results showed a good correlation between each other. This assured us that XiO bolus was been considered by our TPS when calculating.